2020
DOI: 10.1002/ajhb.23384
|View full text |Cite
|
Sign up to set email alerts
|

Weight perception among US adults predicts cardiovascular risk when controlling for body fat percentage

Abstract: ObjectivesPrevious research has revealed that increased obesity prevalence in the US has occurred in concert with an increase in those in overweight and obese BMI categories perceiving their weight as “about right” since the 1980s. Using biological normalcy as a framework, we assess whether individual weight perception is related to the risk of cardiovascular disease (CVD) when controlling for body fat percentage (BF%).MethodsData from the National Health and Nutrition Examination Survey (1999‐2006) included w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Americans are now more likely to underestimate their own BMI, the BMI of their children, and the BMI of others around them compared to previous decades. Perceptions of weight and health have been shown to be causally structured by the body types people typically see and interact with in their daily surroundings, 49 and it has been demonstrated that US adults who perceive their own weight as “about right” vs “overweight” have a lower 10‐year risk of a cardiovascular event occurring, regardless of body fat percentage 50 …”
Section: Discussionmentioning
confidence: 99%
“…Americans are now more likely to underestimate their own BMI, the BMI of their children, and the BMI of others around them compared to previous decades. Perceptions of weight and health have been shown to be causally structured by the body types people typically see and interact with in their daily surroundings, 49 and it has been demonstrated that US adults who perceive their own weight as “about right” vs “overweight” have a lower 10‐year risk of a cardiovascular event occurring, regardless of body fat percentage 50 …”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that this shift in perceived weight status may have negative consequences if it decreases weight loss efforts (Yaemsiri et al, 2011). Conversely, others have argued that being satisfied with one's own weight improves health behaviors and life satisfaction (Blake et al, 2013), and perceiving one's own weight as "about right" rather than "overweight" has been associated with lower cardiovascular risk after controlling for body fat percentage (Cullin & White, 2020). Such changes in perceptions around body fat could be indicative of shifts in social norms in response to the steady rise in average weight status in the US.…”
Section: Obesity Prevalence and Views Of Fatmentioning
confidence: 99%
“…Weight perception may also be related to body size norms and health. Research has indicated that as the prevalence of obesity has increased over the past several decades, so has the likelihood of US adults (Johnson‐Taylor et al, 2008; Maynard et al, 2006) and adolescents (Lu et al, 2015) falling into overweight and obese BMI categories to perceive their own weight as “about right” rather than “overweight.” Furthermore, a recent study found that US adults who perceived their own weight as “about right” had a reduced 10‐year risk of experiencing a cardiovascular event compared to those perceiving their own weight as “overweight,” regardless of body fat percentage (Cullin & White, 2020). Thus, weight perception has been associated with health outcomes independent of body fat itself.…”
Section: Introductionmentioning
confidence: 99%